KERAGAMAN MIKOFLORA TANAH SUPRESIF DALAM MENGENDALIKAN PENYAKIT AKAR GADA PADA TANAMAN KUBIS (BRASSICA OLERACEA L.) - Darmiati, Ni Nengah; Sudarma, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 11 No 1 (2017)DO - 10.24843/EJES.2017.v11.i01.p11, 2017)
DIVERSITY OF SUPRESSIVE LAND MICROFLORA IN CONTROL OF PALLDER DISEASE IN CUBES PLANT (BRASSICA OLERACEA L.) Cabbage ( Brassica oleracea L.) was a vegetable crops cultivated in the highlands to meet the needs of the community vegetable. The main obstacle was the cultivation of cabbage root disease outbreak mace (clubroot), which until now have not found an effective control techniques. Clubroot disease caused by organisms that resemble fungi: Plasmodiophora brassicae Wor. which was the soil inhibitant and soil borne pathogen. Therefore, there must be a way to control environmentally friendly by using suppressive soil, find microbes antagonists related to the cabbage plant habitat in the soil. The results showed that the index of diversity both on suppressive and conducive soil of 1.2304 and 1.2811 respectively, and the index of dominance on the suppressive and conducive soil were 0.6677 and 0.6838.  Prevalence micoflora of the suppressive soil amounted to 44.22 % and 43.06 % conducive soil all dominated by Fusarium spp. Microbial antagonist as a potential control of P. brassicae was Trichoderma sp. Based on the analysis in the suppressive soil as much as 171 x 10 3 cfu /g soil, higher than on the conducive soil to 90 x 10 3 cfu /g soil.